Analisis Penawaran Tenaga Kerja Dosen PTN di Luar Tugas Pokok PNS - Madris, M (Jurnal Trikonomika, 2011)
Peopleâs choice either to work or not theoretically is determined by the level of salary prevailing in the market, non labor income and degree of education as well as work experience of theirs. Lecturers have also work opportunities outside their main duty as civil servant (PNS). This research aims to know the influence of main work load, salary and functional allowance, work retention, chance for pursuing further education, performance and additional income on the labor supply of lecturers outside their main duty as civil servant. This research utilizes prime data with sample of lecturers as many 220 persons with minimum degree of education is post graduate (S2) and class IIIc. This sample is chosen by employing purposive sampling method. By utilizing regression analysis, the result obtained shows that among the six variables influencing labor supply of lecturers working as civil servants at government owned universities, there are four variables which have significant influence; they are main work load, salary or functional allowance, performance and additional income. The chance to get further education as well as work retention do not have significant influence on the use of spare time of lecturers at government owned universities outside their main duty as civil servant in the city of Makassar.